2017
DOI: 10.1021/acs.inorgchem.6b02920
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Coordination of B12F122–, B12Cl122–, and B12H122– to Na+ in the Solid State: Crystal Structures and Thermal Behavior of Na2(B12F12), Na2(H2O)4(B12F12), Na2(B12Cl12), and Na2(H2O)6(B12Cl12)

Abstract: The synthesis of high-purity NaBF and the crystal structures of Na(BF) (5 K neutron powder diffraction (NPD)), Na(HO)(BF) (120 K single-crystal X-ray diffraction (SC-XRD)), Na(BCl) (5 and 295 K NPD), and Na(HO)(BCl) (100 K SC-XRD) are reported. The compound Na(HO)(BF) contains {[(Na(μ-HO)Na(μ-HO))]} infinite chains; the compound Na(HO)(BCl) contains discrete [(HO)Na(μ-HO)Na(HO)] cations with OH···O hydrogen bonds linking the terminal HO ligands. The structures of the two hydrates and the previously published s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 64 publications
0
40
0
Order By: Relevance
“…[Ph 3 C] [ ; Et 2 O [516] ;thf [516] [CB 11 (CF 3 ) 12 ] À Cs [100] * [RCB 11 (F) n (CF 3 ) 11-n ] À R = H, n = 0C s [101] *; n = 1Cs [101] ; n = 5Cs [101] ;n= 6C s [101] ; R = Et, n = 5C s [101] ; R = C 5 H 9 ,n= 5C s [101] [B 12 X 12 ] 2À X = F: Li 2 [106] ;N a [519] ;K 2 [106,519] X = Cl:Li 2 [103] ;Na 2 [103] ;K 2 [103] Na 2 -(OH 2 ) 2.5 [104] ;R b 2 [520] ;Cs 2 [103][104][105] ; X = Br:Na 2 [520] ; Cs 2 [104] ; X = I: Na 2 [520] Na 2 (OH 2 ) 2 [104] ;Cs 2 [104] ; [Cs(NCMe) 2 ] 2 [521] X = Cl:Zn-(OH 2 ) 7 [104] ; X = F: Ag 2 [522,523] ;[Ag(NCMe) 2 ] 2 [523] ;…”
Section: Resultsmentioning
confidence: 99%
“…[Ph 3 C] [ ; Et 2 O [516] ;thf [516] [CB 11 (CF 3 ) 12 ] À Cs [100] * [RCB 11 (F) n (CF 3 ) 11-n ] À R = H, n = 0C s [101] *; n = 1Cs [101] ; n = 5Cs [101] ;n= 6C s [101] ; R = Et, n = 5C s [101] ; R = C 5 H 9 ,n= 5C s [101] [B 12 X 12 ] 2À X = F: Li 2 [106] ;N a [519] ;K 2 [106,519] X = Cl:Li 2 [103] ;Na 2 [103] ;K 2 [103] Na 2 -(OH 2 ) 2.5 [104] ;R b 2 [520] ;Cs 2 [103][104][105] ; X = Br:Na 2 [520] ; Cs 2 [104] ; X = I: Na 2 [520] Na 2 (OH 2 ) 2 [104] ;Cs 2 [104] ; [Cs(NCMe) 2 ] 2 [521] X = Cl:Zn-(OH 2 ) 7 [104] ; X = F: Ag 2 [522,523] ;[Ag(NCMe) 2 ] 2 [523] ;…”
Section: Resultsmentioning
confidence: 99%
“…118 Interestingly, they concluded that B 12 Cl 12 2− coordinates Na + less strongly than B 12 F 12 2− and ultimately suggest that both perfunctionalized dodecaborate derivatives, in their dehydrated forms, may be viable candidates for ion conductivity in energy storage applications.…”
Section: Applications In Catalysis and Materials Chemistrymentioning
confidence: 99%
“…Anion substitution with iodine stabilizes a high temperature polymorph with ion conductivity up to 3.2 mS cm −1 at room temperature [201]. Partly or fully halogenated closo-boranes may in future be useful to create new materials with higher conductivities [202,203].…”
Section: Complex Metal Hydrides As Electrolytesmentioning
confidence: 99%